Situações de vizinhança no condomínio edilício: soluções de conflito, mediação e paz social - aspectos filosóficos, urbanísticos e ambientais - Wagner, Michel Rosenthal (2014)
The study of the neighborhood situation in the multi-ownership condominium aims at drawing a parallel between the provisions of the Civil Code on the subject in terms of ensuring health, peace and safety in the use of real estate. The work seeks to draw attention to the responsibilities of the condominiums for the construction of cities; therefore, several objections involving such living spaces included in the urbanization are analyzed. The Brazilians prefer the vertical model of urban construction with condominiums, and such model has been multiplying, resulting in a high population density. The cities are characterized by being a meeting and exchange point between people, urban citizens, and should be prepared for good living, working and entertaining; however, urban violence has been growing at rates never recorded before in the Brazilian society creating new nuances in the neighborhood status. Therefore, the mediation in conflicts emerging in condominiums is a tool that reunites and promotes dialogue among their residents who find there a private and protected space to submit their issues. These themes are dealt with, aiming at pointing out social peace as responsibility shared between the Law and those working with it as the need to draft a more effective legislation concerning this objective within the Private Law sphere, indicating the need for the corresponding public policies. The right to sustainable cities is clear in the Brazilian legislation. The most disseminated concept of sustainable development is defined as the one meeting the existent needs without compromising the capacity of future generations to meet their own needs. The sustainable development is shown in the environment, economic, social, political, cultural and historic spheres, and based on such focus some ideas appear guiding this life model and the relationship among urban people. The theme is closely related to the diffuse and collective Human Rights and to the human life condition. The work was outlined under the view of theoretic and philosophic grounds about urban life, describing how the neighborhood has been built and developed in the perspective of sustainability, the multi-ownership condominium as a dwelling model and its corresponding responsibilities in the presented situations, the condominium and urban conflicts as well as their appreciation for mediation